USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN CAREER GUIDANCE AND CAREER COUNSELLING (Innovative professional education, 2025)
The article highlights the domestic and foreign experience in the use of information and communication technologies in vocational guidance and consulting a career of student youth. The relevant portals that function in Ukraine and abroad are considered. The directions of use of information and communication technologies in vocational guidance and career counseling are identified
Keywords: information and communication technologies, career counseling, vocational guidance, student youth